Clinical, phenotype and genotype correlations in primary ciliary dyskinesia suspected children in Egypt - Rizk, Hoda; Hjeij, Rim; Al-Haggar, Mohammad; Dworniczak, Bernd; Otto, Dominik; Olbrich, Heike; Osman, Engy; Omran, Heymut; Eldesoky, Tarek (Frontiers in Molecular Biosciences, 2025)
IntroductionPrimary ciliary dyskinesia (PCD) is a rare hereditary disorder affecting mucociliary clearance due to ciliary dysfunction. This study aimed to confirm PCD diagnosis in clinically suspected Egyptian individuals and assess genotype-phenotype correlations.Methods73 PCD-suspected individuals underwent clinical examination, radiological evaluation (chest and sinus CT), and Next-Generation Sequencing (NGS) for a PCD multigene panel. Immunofluorescence (IF) analysis was used to confirm the pathogenicity of identified variants.ResultsConsanguinity was reported in 91.9% of cases, with delayed diagnoses spanning 1–18 years. All individuals exhibited a chronic wet cough; 97.3% experienced nasal congestion, 86.5% chronic sinusitis, 75.7% recurrent otitis media, 37.8% finger clubbing, and 24.3% situs abnormalities. Bronchiectasis was demonstrated in 70.3%, and 18.9% had undergone lobectomies. 37 children carried 26 distinct variants in 16 PCD-related genes (50.7%). Defects were found in outer dynein arms (32%), central pair (19%), radial spokes (16%), ciliogenesis (14%), nexin-dynein regulatory complexes (11%), and other ciliary processes (8%). Moreover, IF analysis revealed the deficiency of corresponding ciliary proteins confirming the pathogenicity of the variants.DiscussionGenetic testing confirmed PCD in 50.7% of cases; based on published TEM-detectable ultrastructural defects, only 40.5% would likely have been detectable by TEM alone, highlighting the need for advanced diagnostics.